Bad Girls of Japan - Miller, L. author. aut Link
XII, 222 p.
Keywords: Are bad girls casualties of patriarchy, a necessary evil, or visionary pioneers? The authors in this volume propose shifts in our perceptions of bad girls by providing new ways to understand them through the case of Japan. By tracing the concept of the bad girl as a product of specific cultural assumptions and historical settings, Bad Girls of Japan maps new roads and old detours in revealing a disorderly politics of gender. Bad Girls of Japan explores deviancy in richly diverse media: mountain witches, murderers, performance artists, cartoonists, schoolgirls and shoppers gone wild are all part of the terrain.